Nuevo enfoque combinatorio para el problema del paseo al azar en un espacio n-Dimensional (ING) - Medina, Víctor; Láscaris Comneno, Tatiana; Skliar, Osvaldo (Uniciencia, 1994)
We present a new combinatorial approach to compute the transition probability corresponding to an arbitrary pair of positions of a particle which follows a random walk on an n-dimensional lattice.The formulas presented here differ in form from the ones previously obtained for the same problem with another approach. Obviously the same numerical results follow from either one of these two approaches.